Svalbardforskning og Svalbardpolitikk 1870-1925. Forskere som politiske aktører - Drivenes, Einar-Arne (University of Tromsø, 2012)
The research and commercial activity in the Scandinavian portion of the Arctic increased appreciably in the last decades of the 19th century and up until the 1920s. Not unexpectedly, the idea arose during this period to bring the largest group of the as yet unclaimed Arctic islands, Spitsbergen, under Norwegian or Swedish control. Norwegian political ambitions in the far north seem to have expanded proportionally with economic and scientific activity. What role did science play in this process? In the contest to win Svalbard, Norwegian authorities deliberately used research results and research activity as justification that Spitsbergen was Norwegian. Also, Spitsbergen researchers worked systematically towards a Norwegian conquest of the archipelago, economic and cultural at first, but ultimately political